Editorial - García Zapata, Teonila Doria (2016)
The Editorial Committee of the “Industrial Data” Journal greets all its readers, and this time presents papers by national and international researchers, some authors are university professors, graduate students, who have written with rigorous and strict adherence to the regulations required to position the magazine at national and international level.